Gait characteristics in people with Friedreich ataxia: daily life versus clinic measures - Casey, Hannah L.; Shah, Vrutangkumar V.; Muzyka, Daniel; McNames, James; El-Gohary, Mahmoud; Sowalsky, Kristen; Safarpour, Delaram; Carlson-Kuhta, Patricia; Rummey, Christian; Horak, Fay B.; Gomez, Christopher M. (Frontiers in neurology, 2025)
Gait assessments in a clinical setting may not accurately reflect mobility in everyday life. To better understand gait during daily life, we compared measures that discriminated Friedreich ataxia (FRDA) from healthy control (HC) subjects in prescribed clinic tests and free, daily-life monitoring. We recruited 9 people with FRDA (median age: 20, IQR [12, 48] years). A comparative healthy control (HC) subject cohort of 9 was sampled using propensity matching on age (median age: 18 [13, 22] years). Subjects wore 3 inertial sensors (one each foot and lower back) in the laboratory during a 2-min walk at a natural pace, followed by 7 days of daily life. For daily life analysis, a total of 99,216 strides across 1,008 h of recording were included. Mann-Whitney U test and area under the curve (AUC) compared gait differences between FRDA and HC when assessed in the laboratory and daily life. Pairwise Wilcoxon tests also compared if participants exhibited different metric values between the two environments. The FRDA group exhibited lower levels of daily activity. Measures that best discriminated gait characteristics of FRDA from HC differed between environments. Variation in elevation of the feet at midswing best discriminated in-clinic (Clinic AUC = 1, Home AUC = 0.69), whereas slow gait speed performed best in daily life (Home AUC = 1, Clinic AUC = 0.64). Of the 17 measures tested, 11 had an AUC > 0.8 in-clinic and 8 had an AUC >0.8 at home. Variability of swing time (Clinic AUC = 0.97, Home AUC = 0.94) and double-support time (Clinic AUC = 0.94, Home AUC = 0.94) were the most sensitive and specific for FRDA in both environments. Digital gait characteristics from inertial sensors are sensitive and specific for FRDA in both environments. However, different gait measures were more sensitive and specific during free-living versus prescribed gait, suggesting that in-clinic gait does not reflect daily life gait.